On n-fold fuzzy implicative/commutative ideals of BCK-algebras - Young Bae Jun (International Journal of Mathematics and Mathematical Sciences)
We consider the fuzzification of the notion of an n-fold implicative ideal, an n-fold (weak) commutative ideal. We give characterizations of an n-fold fuzzy implicative ideal. We establish an extension property for n-fold fuzzy commutative ideals.